Characterizing the ultrastructure of primary ciliary dyskinesia transposition defect using electron tomography. Issue 5 (25th March 2014) - Burgoyne, Thomas; Lewis, Amy; Dewar, Ann; Luther, Pradeep; Hogg, Claire; Shoemark, Amelia; Dixon, Mellisa
<x xml:space="preserve">Abstract</x> Primary ciliary dyskinesia is an autosomal recessive disorder affecting the motility of cilia. There are a range of ultrastructural ciliary defects that lead to associated clinical symptoms including ineffective mucus clearance, reduced lung function, infertility, and left‐right isomerism. Mutations in radial spoke head proteins are a known cause of primary ciliary dyskinesia. Ultrastructually these defects are identified by a portion of cilia lacking a central pair and transposed outer microtubular doublets. We have repeatedly observed an intermittent loss of the central pair in patients with a transposition defect. To further understand the central pair changes in these radial spoke head mutations we employ electron tomography, a high resolution electron microscope technique, to elucidate in three dimensions the ultrastructural arrangements caused by mutation of the RSPH4A gene. We thereby provide an explanation of the structures observed by conventional electron microscopy studies. We demonstrate that the central pair can be present within the cilium. In some cilia, the central pair rotates at the base of the axoneme. We propose that it is this rotation that gives rise to an intermittent appearance of the central pair when viewed under conventional electron microscopy. We discuss the potential causes and consequences of these findings. © 2014 Wiley Periodicals, Inc.